Perspectives in Formulating Policies to Promote Lifelong Learning in the System of Cultural Institutions Towards Building A Learning Society to Meet the Requirements of Digital Transformation in Vietnam - Tung Son, Le (VNU Journal of Science: Policy and Management Studies; Vol 38 No 3DO - 10.25073/2588-1116/vnupam.4405, 2022)
Lifelong learning towards creating a learning society is one of the contemporary issues in the policy and management of culture and education. This is considered as an important key for citizens of each country to survive and develop in a constantly changing world. As a result of this pressing need, each country must develop policies to promote lifelong learning through different models and methods, one of which is lifelong learning in the cultural institutional system. This special model has a dual effect: promoting the building of culture and people while also promoting education towards sustainable development. By analyzing, synthesizing and generalizing the current state of Vietnam's policies as researched in the context of digital transformation, the study points out new trends in policies to promote lifelong learning activities in Vietnam. The system of cultural institutions aims to build a learning society in the contemporary trend based on the philosophy: to create an open, unified, synchronous, connected system of cultural institutions on a digital transformation platform. Keywords : Lifelong learning, cultural institutions, digital transformation cultural and educational policy.